DEMOGRAPHIC CHARACTERISTICS OF HOUSING ESTATES DEVELOPED WITH ISSB TECHNOLOGY IN SELECTED SOUTHWESTERN NIGERIAN (SWN) CITIES - Ibitoye, Obafemi Adeniyi; Abiola, Oyewole A.; Babamboni, Adekunle S. (FUDMA JOURNAL OF SCIENCES, 2023)
Interlocking Stabilized Soil Blocks (ISSB) is a locally available indigenous building material that has been promoted by united nations, ISSB promoters and built environment experts as a sustainable construction material. Research efforts have shown that ISSB offers reasonable benefits over conventional blocks. Nowadays, notable ISSB promoters, stakeholders, and residential estates built using ISSB techniques are rapidly appearing in SWN and surrounding areas. This study aimed at examining the demographic characteristics of ISSB buildings of selected estates in Southwest Nigeria (SWN) towards promoting awareness on ISSB as an alternative construction material in Nigeria. Datas were collected from interviews, observations, and documentaries from ISSB promoters and users of ISSB buildings in SWN. The study found that the following estates in SWN were built with ISSB: Obasanjo Estate, Ekiti with a total of One hundred and fourty eight(148) completed buildings; Redemption city, Mowe Ogun state with a total of forty eight (48) completed buildings; Amen estate, Lagos state with a total of three hundred (300) completed housing units. Based on the demographics of ISSB buildings shown in this study, the population’s preference for ISSB as the preferred building material is relatively low when compared with Sandcrete blocks. However, ISSB is becoming increasingly attractive as a sustainable construction material in Southwest Nigeria. In conclusion, the study suggested that with an increasing awareness about ISSB, improving technologies, increasing the number of promoters of ISSB, and government support, ISSB will quickly become the affordable building material of choice in Nigeria.
Keywords: Affordable Housing; Alternative Building material; Interlocking Stabilized Soil Blocks